2020
DOI: 10.1002/pro.3994
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiscs: A toolkit for membrane protein science

Abstract: Membrane proteins are involved in numerous vital biological processes, including transport, signal transduction and the enzymes in a variety of metabolic pathways. Integral membrane proteins account for up to 30% of the human proteome and they make up more than half of all currently marketed therapeutic targets. Unfortunately, membrane proteins are inherently recalcitrant to study using the normal toolkit available to scientists, and one is most often left with the challenge of finding inhibitors, activators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 220 publications
(247 reference statements)
0
73
0
2
Order By: Relevance
“…While these experiments were conducted with receptor reconstituted in detergent, functional, pharmacological, and 19 F-NMR spectroscopic characterization of the b 2 AR in synthetic lipid disks [nanodisks or reconstituted high-density lipoprotein (rHDL) particle (reviewed in Ref. [104])] containing the phospholipids 1-palmitoyl-2-oleoyl-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1 0 -racglycerol) (POPG) revealed a much higher basal activity and a greatly increased population of an active state in the absence of ligands than in detergent micelles [75]. Based on NMR line shape analysis, it was found that these differences are due to a significantly slower exchange rate (millisecond time range) between the active and inactive states of the receptor in a lipid environment compared to detergent micelles.…”
Section: Unliganded Statementioning
confidence: 99%
“…While these experiments were conducted with receptor reconstituted in detergent, functional, pharmacological, and 19 F-NMR spectroscopic characterization of the b 2 AR in synthetic lipid disks [nanodisks or reconstituted high-density lipoprotein (rHDL) particle (reviewed in Ref. [104])] containing the phospholipids 1-palmitoyl-2-oleoyl-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1 0 -racglycerol) (POPG) revealed a much higher basal activity and a greatly increased population of an active state in the absence of ligands than in detergent micelles [75]. Based on NMR line shape analysis, it was found that these differences are due to a significantly slower exchange rate (millisecond time range) between the active and inactive states of the receptor in a lipid environment compared to detergent micelles.…”
Section: Unliganded Statementioning
confidence: 99%
“…For instance, it was initially observed that the human γ -secretase yielded a higher-resolution cryo-EM structure in APol A8-35 than in digitonin (Lu et al ., 2014), whereas, a few years later, using a version of γ -secretase fused with T4 lysozyme, two other structures were obtained in digitonin at a higher resolution than that initially achieved in A8-35 (Yang et al ., 2019; Zhou et al ., 2019). Beyond some obvious limitations, such as the fact that current membrane scaffold protein (MSP)-based NDs (Denisov and Sligar, 2017; Sligar and Denisov, 2020) cannot accommodate MPs with very large transmembrane domains and thus are not appropriate for studying large supercomplexes (see below), trial-and-error is still the only way to proceed. Yet, examining the set of all MP structures determined to-date by SP cryo-EM reveals some interesting trends that can help selecting the most promising tools.…”
Section: Selection Of Reportsmentioning
confidence: 99%
“…Finally, protein-based NDs are nanometric-sized objects of discoidal shape formed by lipid bilayer patches stabilized by two encircling amphipathic helical proteins derived from apolipoprotein A1, called MSPs (Fig. 6a; for recent reviews, see Denisov and Sligar, 2017; Denisov et al ., 2019; Sligar and Denisov, 2020). The total number of MP structures established in MSP-based NDs at resolutions ⩽5 Å is 100.…”
Section: An Overview Of Surfactant Usage At the Vitrification Stepmentioning
confidence: 99%
“…Following the first account of a lipid nanodisc surrounded by membrane scaffold protein (MSP) [124], several other types of scaffolds have been described, including saposin proteins (salipro) [125], as well as copolymer-scaffolded nanodiscs utilizing styrene-maleic acid (SMA) and diisobutylene/maleic acid (DIBMA) [126,127]. The formation of nanodiscs follows similar principles as the formation of bicelles, starting from a mixture of detergentsolubilized lipid, detergent-solubilized protein, and MSP or saposin, respectively, and is driven by subsequent detergent removal [125,128,129].…”
Section: Bicelles and Nanodiscsmentioning
confidence: 99%